The Self-Passivation Mechanism in Degradation of BiVO4 Photoanode - Yao, Xin; Zhao, Xin; Hu, Jun; Xie, Huiqing; Wang, Danping; Cao, Xun; Zhang, Zheng; Huang, Yizhong; Chen, Zhong; Sritharan, Thirumany (iScience, 2019)
BiVO4 is a promising photoanode material for solar-assisted water splitting in a photoelectrochemical cell but has a propensity to degrade. Investigations carried out here in 0.1 M Na2SO4 electrolyte showed that degradation is by dissolution of V in the electrolyte while Bi is retained on the anode probably in the form of solid Bi oxide (Bi2O3, Bi4O7). Accumulation of Bi oxide on the anode surface leads to passivation from further degradation. Thermodynamic modeling of possible degradation reactions has provided theoretical support to this mechanism. This self-passivation is accompanied by a decrease in photocurrent density, but it protects the anode against extensive photocorrosion and contributes to long-term stability. This is a more definitive understanding of degradation of BiVO4 during water splitting in a photoelectrochemical cell. This understanding is imperative for both fundamental and applied research. [Display omitted] •A mechanism of degradation is developed for BiVO4 photoanode during photolysis•Degradation occurs by V dissolution and Bi accumulation on the anode as oxide•Accumulating Bi oxide passivates the anode•Thermodynamic modeling supports this mechanism Electrochemical Energy Storage; Electrochemical Energy Conversion; Chemical Reactions in Materials Science; Materials Characterization